1994
DOI: 10.1159/000168710
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Alterations during Hemodialysis: Insights from New Noninvasive Technology

Abstract: Eighteen patients with chronic renal failure had their cardiac status monitored during hemodialysis (HD). Ten studies were carried out using an ambulatory nuclear vest to assess ejection fraction (EF), heart rate (HR), relative end-systolic (ESV) and end-diastolic (EDV) volumes every 60 s. A total of 36 episodes of EF falls occurred in 9 patients, all asymptomatic. These EF falls were associated with a rise in ESV, while HR, BP, and EDV remained unchanged. The EF falls correlated best with the volume of ultraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The characterization of these defects is difficult since some worsen while others improve with dialysis (tables 2, 3). This phenomenon has been found in a previous study using sestamibi imaging in dialysis patients [15]. …”
Section: Discussionsupporting
confidence: 80%
“…The characterization of these defects is difficult since some worsen while others improve with dialysis (tables 2, 3). This phenomenon has been found in a previous study using sestamibi imaging in dialysis patients [15]. …”
Section: Discussionsupporting
confidence: 80%
“…Repeated episodes of stunning are cumulative and contribute to the pathophysiology of heart failure (4). We and other investigators have previously shown evidence that subclinical ischemia occurs in response to the stress of hemodialysis (5)(6)(7). We also demonstrated that it was possible to reduce the frequency and the severity of this phenomenon by using biofeedback dialysis (Hemocontrol, Gambro-Hospal, Mirandora, Italy) to improve the hemodynamic tolerability of dialysis.…”
mentioning
confidence: 59%
“…Intradialytic hypotension increases the risk of myocardial hypoperfusion, leading to segmental ischemia inducing segmental left ventricular (LV) dysfunction [8], a process known as myocardial stunning [9]. Myocardial stunning is cumulative and leads to irreversible LV dysfunction in ischemic heart disease [10,11]. …”
Section: Introductionmentioning
confidence: 99%